The Effects of Physician Characteristics on Patients’ Hospital Discharge Destination and Length of Stay - Lara Gardner; Sharmila Vishwasrao (Research in Applied Economics, 2024)
We study the effects of physician, hospital, and market characteristics on length of stay and discharge destinations for cardiac inpatients in Florida hospitals in 2004, while controlling for patient characteristics. Using a competing risks hazard model, we analyze the determinants of whether patients are discharged home, to a skilled nursing facility, home under the supervision of a home health agency, or die within the hospital. Our study is unique in that we estimate a competing risks hazard model to identify the impact of physician education and training on hospital length-of-stay and post-hospital discharge destination. We find that physician characteristics are significantly related to transition rates to home discharge and that hospital and county characteristics impact the hazard rates for discharge to home health agencies and skilled nursing facilities.